Regio‐ and Enantioselective γ‐Allylic Alkylation of In Situ‐Generated Free Dienolates via Scandium/Iridium Dual Catalysis - Zhang, Jian; Yang, Wu‐Lin; Zheng, Hanliang; Wang, Yi; Deng, Wei‐Ping (Angewandte Chemie International Edition, 2022)
An unprecedented asymmetric γ‐allylic alkylation of free dienolates via Sc/Ir dual catalysis is reported, which affords a range of synthetically versatile γ‐allylic crotonaldehydes in high efficiency with excellent chemo‐, regio‐, and enantioselectivities. The dienolates bearing no essential auxiliary groups were generated in situ by scandium triflate‐mediated Meinwald rearrangement of vinyloxiranes atom‐economically. With the assistance of computational density functional theory calculations, a Sc/Ir bimetallic catalytic cycle was proposed to illustrate the reaction mechanism. The first Ir‐catalyzed asymmetric γ‐allylic alkylation of free dienolates, generated in situ by Sc‐mediated Meinwald rearrangement of vinyloxiranes has been established. This protocol affords synthetically versatile γ‐allylic crotonaldehydes in high efficiency with excellent regio‐ and enantioselectivities.